2001
DOI: 10.1046/j.0966-0410.2001.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in informal care in Great Britain during the 1990s

Abstract: The population of adult carers in Great Britain declined during the 1990s while the proportion of those heavily involved in providing informal care increased. The intensification of care-giving was associated with an increasing number of caring relationships that typically make heavy demands on the carer: spouse care and caring for a child or parent. The provision of informal care by friends and neighbours diminished resulting in an overall decline in care-giving between households. However, parents were incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 11 publications
2
70
1
2
Order By: Relevance
“…There is emerging evidence that some men are assuming the tasks and responsibilities of caring, and this presents generalized and gender-specific issues related to caring roles (Hirst, 2001;Spillman & Pezzin, 2000). Men may feel uncomfortable in caring roles because they contradict dominant ideals and practices of masculinity that imply that men are biologically ill suited to the emotional tasks of caring.…”
Section: Men and Caringmentioning
confidence: 99%
“…There is emerging evidence that some men are assuming the tasks and responsibilities of caring, and this presents generalized and gender-specific issues related to caring roles (Hirst, 2001;Spillman & Pezzin, 2000). Men may feel uncomfortable in caring roles because they contradict dominant ideals and practices of masculinity that imply that men are biologically ill suited to the emotional tasks of caring.…”
Section: Men and Caringmentioning
confidence: 99%
“…It is suggested that this is not an uncommon concept, with an increasing number of females caring for parents and parent in-laws in general (Hirst, 2001). These findings from Adamson and Donovan (2005) appear to relate to those of Botsford et al (2011) and in females holding an existing, moral obligation to care that may not be seen as much in male carers.…”
Section: Female Responsibilitymentioning
confidence: 99%
“…marketers) to create fairness in the marketplace' and which includes both perceived 3 and actual 4 vulnerability. This state is also central to the work of Hirst (2001) and Howard (2001), both of whom comment upon the growing body of carer research linked to tackling the adverse consequences of caring upon consumer mental and physical well-being. It is also a feature of the work of Mason and Pavia (2006) who explore the vulnerability felt by families caring for children with special needs.…”
Section: Caring and Consumer Vulnerabilitymentioning
confidence: 95%